Surveillance of de novo head and neck cancer in liver transplant recipients allows an early diagnosis: a retrospective analysis of a surveillance program - Zambrano, Ivan; Alcalde, Juan; Iñarrairaegui, Mercedes; Rotellar, Fernando; Herrero, J. Ignacio (Frontiers in Oncology, 2025)
IntroductionDe novo head and neck cancer is a common and severe complication than can occur after liver transplantation. However, it is unclear whether surveillance can help detect and prevent this type of cancer in liver transplant recipients.Patients and methodsWe retrospectively examined 119 transplanted patients who had a smoking history above 20 pack-years. These patients underwent yearly evaluations by an ear-nose-throat specialist.ResultsTwelve of them (10.1%) were diagnosed with head and neck cancer. The most significant risk factor for developing head and neck cancer was having been transplanted for alcoholic liver disease. Of the 12 diagnosed cases, six cases were diagnosed at an early-intermediate stage (stages 0-II), five were at an advanced stage (including one patient who was diagnosed at his first surveillance visit and two who did not attend the surveillance visits), and tumor stage was unknown in one case. Three patients had cancer recurrences, all of them had continued smoking after their initial diagnosis. The five-year actuarial survival rate after the diagnosis of head and neck cancer was 65.6%.DiscussionAnnual surveillance for head and neck cancer may allow for early diagnosis and better survival rates after cancer diagnosis.